Extreme Temperature and Extreme Violence across Age and Gender: Evidence from Russia - Olga Popova; Vladimir Otrachshenko; José Tavares (Global Labor Organization (GLO), 2019)
We examine the relationship between extreme temperatures and violent mortality across Russian regions, with implications for the social costs of climate change. We assess the unequal impact of temperature shocks across gender and age groups by exploring a dataset on temperature and violence in Russia, between the years 1989 and 2015. Hot days lead to an increase in both female and male victims, one hot day resulting in the loss of 1,579 person-years of life for men, and 642 for women. However, the likelihood of victimization during weekends rises noticeably for women, with women between 25 and 59 more victimized on weekends. Our results suggest that female victimization on hot days would be mitigated by increases in regional income and job opportunities, and on cold days, by decreasing the consumption of spirits.
Keywords: I14; K42; P52; Q54; 330; Violence; Gender Homicide; Extreme Temperatures; Russia